Continuous positive airway pressure and liver enzymes in obstructive sleep apnoea: data from a randomized controlled trial. - Kohler, M; Pepperell, J; Davies, R; Stradling, JR (2009)
BACKGROUND: Obstructive sleep apnoea syndrome (OSAS) has been suggested to be an independent risk factor for non-alcoholic fatty liver disease (NAFLD), possibly via intermittent hypoxia that influences blood pressure, lipid levels and insulin resistance, factors themselves known to cause NAFLD. In observational studies, OSAS has been associated with elevated levels of liver enzymes. Continuous positive airway pressure (CPAP) is the treatment for OSAS, but the effects of CPAP on liver enzymes have not been studied in a randomized controlled trial. OBJECTIVE: To determine if 4 weeks of CPAP influence alanine-aminotransferase (ALT) and aspartate-aminotranferase (AST) levels. METHODS: 94 patients with moderate-to-severe OSAS were randomized to therapeutic or sub-therapeutic CPAP treatment. Plasma ALT and AST were measured before and after 4 weeks of CPAP. RESULTS: Results are means +/- SD. ALT levels decreased from 39.1 +/- 26.3 to 30.3 +/- 16.4 IU/l in patients treated with therapeutic CPAP, but also decreased from 36.9 +/- 20.7 to 31.5 +/- 16.5 IU/l in patients treated with sub-therapeutic CPAP (difference between mean changes -3.4, 95% CI -7.8 to 1.0 IU/l, p = 0.13 between groups). AST levels did not change significantly with therapeutic CPAP (from 29.1 +/- 14.7 to 30.2 +/- 13.6 IU/l), nor with sub-therapeutic CPAP (from 28.2 +/- 16.2 to 29.5 +/- 12.6 IU/l; difference between mean changes -0.2, 95% CI -3.0 to 2.6 IU/l, p = 0.87 between groups). CONCLUSIONS: Four weeks of active CPAP has no beneficial effect on aminotransferase levels when compared to sub-therapeutic CPAP in patients with OSAS. Therefore, CPAP does not seem to improve biochemical markers of potential NAFLD in OSAS patients.